2018
DOI: 10.3389/fimmu.2018.02473
|View full text |Cite
|
Sign up to set email alerts
|

The Vacuolar Pathway in Macrophages Plays a Major Role in Antigen Cross-Presentation Induced by the Pore-Forming Protein Sticholysin II Encapsulated Into Liposomes

Abstract: Cross-presentation is an important mechanism for the differentiation of effector cytotoxic T lymphocytes (CTL) from naïve CD8+ T-cells, a key response for the clearance of intracellular pathogens and tumors. The liposomal co-encapsulation of the pore-forming protein sticholysin II (StII) with ovalbumin (OVA) (Lp/OVA/StII) induces a powerful OVA-specific CTL activation and an anti-tumor response in vivo. However, the pathway through which the StII contained in this preparation is able to induce antigen cross-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Previous studies revealed that Sticholysin (St) II, an invertebrate PFP produced by the Caribbean Sea anemone Stichodactyla helianthus belonging to the actinoporin family, was encapsulated into liposome to efficiently enhance the antigen-specific CTL responses as an adjuvant and this may not depend on its pore-forming activity. 64,65 However, βγ-CAT is a vertebrate PFP from the frog B. maxima belonging to the aerolysin family. Importantly, the enhanced antigen presentation induced by βγ-CAT depends on its capacity of pore formation in BMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that Sticholysin (St) II, an invertebrate PFP produced by the Caribbean Sea anemone Stichodactyla helianthus belonging to the actinoporin family, was encapsulated into liposome to efficiently enhance the antigen-specific CTL responses as an adjuvant and this may not depend on its pore-forming activity. 64,65 However, βγ-CAT is a vertebrate PFP from the frog B. maxima belonging to the aerolysin family. Importantly, the enhanced antigen presentation induced by βγ-CAT depends on its capacity of pore formation in BMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-presenting capacities of BM macrophages seem to be higher than BM DCs when tested side-by-side using liposomes encapsulating a mixture of the model antigen ovalbumin and the pore-forming protein sticholysin II. Macrophage colony-stimulating factor–differentiated BM macrophages were better in activating the ovalbumin-recognizing B3Z CD8 + T-cell line (which does not require costimulation) than GM-CSF–differentiated BM-derived DCs in vitro ( 49 ). This could be explained by the lower ability of the DCs to internalize the antigen-containing liposomes ( 49 ).…”
Section: Cellular Pathways Of Cross-presentation By Macrophagesmentioning
confidence: 99%
“…Macrophage colony-stimulating factor–differentiated BM macrophages were better in activating the ovalbumin-recognizing B3Z CD8 + T-cell line (which does not require costimulation) than GM-CSF–differentiated BM-derived DCs in vitro ( 49 ). This could be explained by the lower ability of the DCs to internalize the antigen-containing liposomes ( 49 ). Furthermore, inhibitors of the lysosomal proteases cathepsins and leupeptin resulted in a reduced efficiency of B3Z T-cell activation by the BM macrophages, whereas a proteasome inhibitor (epoxomicin) had no effect ( 49 ).…”
Section: Cellular Pathways Of Cross-presentation By Macrophagesmentioning
confidence: 99%
“…Sticholysins I and II (StI and II) are actinoporins produced by the Caribbean Sea anemone Stichodactyla helianthus (23). These toxins are of current interest as an active component of a vaccine platform (24,25) and of immunotoxin constructs active against tumor cells (26,27). Peptides reproducing the N-terminus of StI sequence 1-31 (StI1-31) and StII sequence 1-30 (StII1-30) ( Figure 1A) can mimic the permeabilizing ability of these toxins in red blood cells and liposomes (10,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Its forms pores in human red blood cells with a similar size to those formed by the full-length toxin (9). StII1-30 has emerged as a good candidate to replace the whole toxins in some biomedical applications such as an active component of a vaccinal platform to promote the delivery of different molecules to the cytosol and enhance the immune response in anti-cancer therapies (24,25). Previously, we have analysed the conformational properties of StI1-31 and StII1-30 in solution and in membrane mimetic systems and their ability to permeabilize lipid vesicles (9,12,13,28,29).…”
Section: Introductionmentioning
confidence: 99%